Violência sexual infantil e suas diferentes formas: uma tradução audiovisual do Português para Libras - Nascimento, Gláucia Cristina Magdalena dos Santos (Universidade Federal de São Carlos, 2023)
The present work consists of the translation for Libras of an informative audiovisual material, available on the Youtube platform entitled “Child sexual violence and its different forms”. This research is located in the field of language studies, with the aim of investigating, analyzing and reflecting on the translation process during the realization of a translation in a community context. The stages of elaboration of the same were gone through, through guidance in which new directions for the coherent development of the addressed topic were clarified. In addition to the supervisor, the production of the work was carried out by a team that included a graduate student of the TILSP course, TILSP interpreter, Coorientation of the Me. audiovisual technician of the TILSP course. It is hoped that the elaboration of this work in team with the material to be translated located in the research of translation studies, will favor the use of the same by professional sign language translators and interpreters currently in the community context, contributing to the construction of accessibility information of social relevance in combating sexual violence against children and adolescents. In addition to providing a reflection to future professional translators and interpreters, on their translation process and the importance of teamwork.
Child sexual violence and its different forms: an audiovisual translation from Portuguese to Libras
Keywords: Tradução; Audiovisual; Violência sexual; Libras; Translation; Sexual violence; LINGUISTICA, LETRAS E ARTES::LINGUISTICA